Fostering Willingness to Communicate: An Investigation of Psychological and Situational Factors in EFL Context - Oktaviani, Zafira Fauziah; Sadikin, Irma Savitri (Universitas Muhammadiyah Mataram, 2025)
Since it measures how prepared students are to use the target language in authentic situations, Willingness to Communicate (WTC) has emerged as a key concept in second and foreign language studies. Despite its importance, there are still few studies conducted in Indonesian higher education, especially when it comes to examining the combined effects of situational and psychological factors on students’ WTC. This study aims to explore how these factors interact and to identify strategies for enhancing communication in English as a Foreign Language (EFL) classroom. Employing a qualitative case study design, the study involved first-year students enrolled in the Speaking for Survival Function course at Esa Unggul University through in-depth interviews and closed-ended questionnaires. The findings reveal that psychological factors, including self-confidence, perceived communicative competence, learning anxiety, motivation, and personality, play a significant role in shaping students’ WTC. In addition, situational factors such as teachers’ roles and attitudes, task types, topics, classroom atmosphere, and interlocutor characteristics strongly influence students’ communicative behavior and engagement. Overall, the findings emphasize the importance of implementing supportive and encouraging instructional strategies to enhance students’ readiness to communicate in English within Indonesian higher education contexts.